LIVING HADIS: Penggunaan Hadis Dalam Ceramah Agama di Radio Majlis Tafsir al-Qur’an - Nadia, Zunly (BINA' AL-UMMAH, 2020)
This article discusses the use of hadith in religious lectures delivered through electronic media, by Majlis Tafsir al-Qur'an (MTA) Surakarta. That living hadith, either being able to contribute  developing the objects of hadith study and can be functional to succeeed  da'wah and community empowerment, as well. Hadist interpretation ideally  not just related to the texts, but also concerns with the socio-cultural context that surrounds it. Basically the aim of interpretation is to understand the skyrocketing messages of God it in the context and reality of human beings in the wordl life. Then, differences arise in terms of interpretation to the way to "treat" the hadith in a practical level in society. This research found the reality that  the nreligious (Islamic) instructors uses textual way in understanding hadists.